Modeling Dysmenorrhea Using PLS-SEM: The Role of Pain Frequency, Severity, and Self-Management among Female Health Students - Karwati Karwati; Heru Santoso Wahito Nugroho (Ahmar Metastasis Health Journal, 2026)
Dysmenorrhea remains a common health issue among young women, yet limited studies have examined the behavioral structure underlying its burden, particularly among female health students. This study aimed to develop and test a structural behavioral model linking menstrual bleeding duration, pain frequency, pain severity, and primary self-management methods. A cross-sectional design was employed involving 215 female health students, with data collected through a structured questionnaire. The analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate the relationships among variables. The findings indicate that menstrual pain frequency significantly predicts pain severity (p < 0.001) and the choice of primary self-management methods (p = 0.034). In contrast, menstrual bleeding duration showed no significant effect on either pain severity or self-management strategies. These results highlight that pain frequency is the key determinant in shaping dysmenorrhea burden and behavioral responses, providing a novel contribution to understanding self-management patterns among health students. The study suggests that interventions should prioritize managing pain frequency to reduce dysmenorrhea impact.